An Early Cretaceous stratigraphic marker fossil in the High Arctic: the belemnite Arctoteuthis bluethgeni. (8th October 2020) - Alsen, Peter; Jelby, Mads E.; Śliwińska, Kasia K.; Mutterlose, Jörg
Abstract: The original description of the large and characteristic belemnite species Arctoteuthis bluethgeni Doyle was based on fragmentary material from a relatively uncertain stratigraphic interval in Kong Karls Land, Svalbard. Recent collection of a belemnite assemblage in the Lower Cretaceous Rurikfjellet Formation on Spitsbergen include numerous complete specimens, allowing a detailed description of the species. With the exception of a specimen reported from Arctic Canada, its distribution is restricted to Svalbard. Its stratigraphic range appears to be restricted to the upper Valanginian – lower Hauterivian from ages obtained from palynostratigraphy. A. bluethgeni is therefore considered to be a useful Lower Cretaceous guide fossil in the Boreal High Arctic.